Análise da relação entre o estilo de vida, aspectos cognitivos, capacidade de compensação cognitiva e níveis de BDNF em idosos - Lima, Daiane Borba de (2017)
It is widely accepted that normal aging is accompanied by changes in cognitive abilities. It is also important to note that the pattern and degree of cognitive alterations in non-demented older adults is heterogeneous, with some of them showing significant impairments while others maintain relatively constant performances throughout aging. Among the factors that seem capable to modulate cognitive integrity on older age is life style. There are a number of suggestions that social, intellectual and physical activities enhance cognitive reserve and protect against cognitive decline. The mechanisms related to these benefits are still unknown, but intervention studies with older adults suggest that BDNF could be a mediator of the benefits on cognitive function induced by physical activity. However, studies on the effects of social and intellectual activities on this neurotrophin are scarce. In the present study, it were evaluated the lifestyle effects (social, intellectual and physical activities) on cognitive aspects and BDNF levels of healthy older adults. The relation between social, intellectual and physical activities, BDNF levels and neuropsychology performance (attention, working memory and executive function tests) was analyzed in a sample of healthy older adults (≥ 60 years old, n=58). The results showed no significant associations between social or intellectual activity levels with BDNF levels, but the group with the lowest level of physical activity had the lowest BDNF levels. Additionally, the findings did not identify consistent effects of these lifestyle components on cognitive functions. Since it is possible that the neuropsychological tests used had not enough sensibility to identify lifestyle effects on cognition, it was investigated a more sensible task: an incidental contextual memory test. Thus, it was evaluated the effect of physical activity on contextual memory of older adults (≥ 60 years old, n=52). It was observed that higher physical activity levels improved free recall and recognition of contextual memory. In addition, the combination of higher physical activity levels and an associative encoding instruction resulted in the better contextual memory in free recall. The results described above indicate that physical activity modulates BDNF levels and has the potential to improve cognitive reserve and cognitive performance. Additionally, the effects of intellectual and social activities are probably not sufficiently robust to be identified in transversal experimental designs of healthy older adults, especially when the subjects operate in a relatively narrow range of these lifestyle aspects.